2021
DOI: 10.1002/hep.31466
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome Profiling Identifies TIGIT as a Marker of T‐Cell Exhaustion in Liver Cancer

Abstract: BACKGROUND AND AIMS Programmed death 1 (PD‐1) checkpoint inhibition has shown promising results in patients with hepatocellular carcinoma, inducing objective responses in approximately 20% of treated patients. The roles of other coinhibitory molecules and their individual contributions to T‐cell dysfunction in liver cancer, however, remain largely elusive. APPROACH AND RESULTS We performed a comprehensive mRNA profiling of cluster of differentiation 8 (CD8) T cells in a murine model of autochthonous liver canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 54 publications
2
54
0
Order By: Relevance
“…27,28 In a variety of tumors, the co-inhibitory molecules TIGIT and TIM-3 are closely related to T cell exhausted. [29][30][31][32] These studies indicate that it is necessary to study the specific exhausted phenotype and function of NK cells in HBV-HCC patients to reveal new anti-tumor targets of NK cells. In this study, we found that the co-expression of TIGIT and TIM-3 mediates NK cells exhaustion in HBV-HCC patients, which is characterized by the decrease of cytokine (IFN-γ, TNF-α), decreased cytotoxicity (CD107a), proliferation (Ki67), and high expression of T-bet lo Eomes hi NK cells in HBV-HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In a variety of tumors, the co-inhibitory molecules TIGIT and TIM-3 are closely related to T cell exhausted. [29][30][31][32] These studies indicate that it is necessary to study the specific exhausted phenotype and function of NK cells in HBV-HCC patients to reveal new anti-tumor targets of NK cells. In this study, we found that the co-expression of TIGIT and TIM-3 mediates NK cells exhaustion in HBV-HCC patients, which is characterized by the decrease of cytokine (IFN-γ, TNF-α), decreased cytotoxicity (CD107a), proliferation (Ki67), and high expression of T-bet lo Eomes hi NK cells in HBV-HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…TIGIT activation in Treg cells leads to T-cell suppression by producing interleukin (IL)-10 and fibrinogen-like protein 2 (35,36). TIGIT expression and clinical outcomes in cancer: Increased TIGIT expression on TILs has been observed in various human cancers, including non-small-cell lung carcinoma (NSCLC), melanoma, head and neck squamous cell carcinoma (HNSCC), colorectal cancer (CRC), glioblastoma (GBM), gastric cancer, liver cancer, multiple myeloma (MM), acute myeloid leukemia (AML), and follicular lymphoma (FL) (15,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). TIGIT-expressing CD8 is correlated with AML relapse and post-allogeneic stem-cell transplantation progression (38).…”
Section: Tigit Family Of Receptors Tigitmentioning
confidence: 99%
“…248 Unfortunately, T cell activity in tumors is limited; chronic stimulation of T cells ultimately leads to a dysfunctional state called T cell exhaustion that has been associated with high levels of PD-1 expression and a low responsiveness to checkpoint blockade. [249][250][251][252] Inhibition of PD-1/PD-L1 can lead to reinvigoration of exhausted T cells and improvement of their anti-tumor activity. 253 Nevertheless, it seems that certain properties of exhausted T cells cannot be reverted.…”
Section: Hcc Arises In a Tolerogenic Immune Microenvironment And Devementioning
confidence: 99%